Bilateral femoral neck fractures as a result of coeliac disease. Issue 675 (January 1982) - Rubinstein, A.; Liron, M.; Bodner, G.; Gefel, A.
Abstract : An elderly patient presenting with severe tetany secondary to hypocalcaemia causing bilateral fractures of the femoral necks, was proved to have coeliac disease. Severe muscle pains, an organic mental syndrome and personality changes are rare complications of coeliac disease and are reversible with treatment.